Minimal domain peptides derived from enterocins exhibit potent antifungal activity - Cohen, Dorrian G.; Heidenreich, Theresa M.; Schorey, Jason W.; Ross, Jessica N.; Hammers, Daniel E.; Vu, Henry M.; Moran, Thomas E.; Winski, Christopher J.; Stuckey, Peter V.; Ross, Robbi L.; Yee, Elizabeth Arsenault; Santiago-Tirado, Felipe H.; et al. (Frontiers in Fungal Biology, 2024)
The antimicrobial peptide (AMP) circularized bacteriocin enterocin AS-48 produced by Enterococcus sp. exhibits broad-spectrum antibacterial activity via dimer insertion into the plasma membrane to form membrane pore structures, compromising membrane integrity and leading to bactericidal activity. A specific alpha-helical region of enterocin AS-48 has been shown to be responsible for the membrane-penetrating activity of the peptide. The canon syn-enterocin peptide library, generated using rational design techniques to have ninety-five synthetic peptide variants from the truncated, linearized, membrane-interacting domain of enterocin AS-48, was screened against three clinically relevant fungal strains: Cryptococcus neoformans, Candida albicans, and Candida auris for potential antifungal activity. Twelve peptides exhibited antifungal activity against C. neoformans, and two peptides exhibited activity against C. albicans. The fourteen active antifungal peptides were minimally cytotoxic to an immortalized human keratinocyte cell line (HaCats). Four select peptides were identified with minimum inhibitory concentrations (MICs) below 8 µM against C. neoformans. In 36-hour cell growth tests with these fungicidal peptides, fungicidal peptide no. 32 displayed inhibitory properties comparable to the leading antifungal medication fluconazole against C. neoformans. Screening of peptide no. 32 against a deletion library of C. neoformans mutants revealed that the mechanism of action of peptide no. 32 may relate to multivesicular bodies (MVBs) or polysaccharide capsule targeting. These findings importantly demonstrate that naturally derived AMPs produced by bacteria can be sourced, engineered, and modified to exhibit potent antifungal activity. Our results will contribute to the development of broad treatment alternatives to fungal infections and lend themselves to direct implications for possible treatment options for C. neoformans infections.